2019
DOI: 10.1016/j.shaw.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health and Occupational Characteristic of Horse Stable Hand Workers in Korea

Abstract: The horse stable hand workers are one of the most important occupations in horse-racing industry. However, suicide problem of the horse stable hand workers in Korea has raised the necessity of new study on how these workers experience mental health problems such as occupational stress and depression in organizational situation. Therefore, this study investigated the occupational stress and depression level of the horse stable hand workers and identified the structural relationship in the horse-racing industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The prevalence of MSDs in various positions of coal miners with severe burnout is much higher than that of coal miners affected by job burnout to a lesser degree, suggesting that there is a certain relationship between job burnout and MSDs in this population and confirming that job burnout is a risk factor for MSDs. Psychosocial factors have been reported to have a noticeable effect on MSDs [37,38], with adverse psychosocial factors shown to change human behavior and lead to the occurrence of MSDs [39] via a two-way feedback between psychosocial factors and MSDs [40]. Studies outside China have also shown that psychological factors and physical load simultaneously influence the prevalence of MSDs [41].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MSDs in various positions of coal miners with severe burnout is much higher than that of coal miners affected by job burnout to a lesser degree, suggesting that there is a certain relationship between job burnout and MSDs in this population and confirming that job burnout is a risk factor for MSDs. Psychosocial factors have been reported to have a noticeable effect on MSDs [37,38], with adverse psychosocial factors shown to change human behavior and lead to the occurrence of MSDs [39] via a two-way feedback between psychosocial factors and MSDs [40]. Studies outside China have also shown that psychological factors and physical load simultaneously influence the prevalence of MSDs [41].…”
Section: Discussionmentioning
confidence: 99%
“…Work environment issues are a major concern for the industry, since it is a laborintensive sector involving long hours, a high physical workload, and low pay [16]. Despite that, research specifically on the working environment in the equine sector is limited [15]. The equine sector has not undergone the same technological development as in the agri-cultural sector, often due to factors such as economics and tradition.…”
Section: The Swedish Equine Sectormentioning
confidence: 99%
“…Furthermore, a stable culture with masculine military norms exists in the sector [32]. In addition, Kim et al [15] showed high levels of occupational stress and problems with mental health among employees in the Korean horse racing industry related to job demand and occupational organization. Overall, the Swedish Work Environment Authority [33] has highlighted failures in the systematic work environment management in the Swedish equine sector.…”
Section: The Swedish Equine Sectormentioning
confidence: 99%
See 1 more Smart Citation